Agroecological management in production of radish fertilized with cow urine - Furlanetto, Angélica Danieli; Martinez, Roberto Antonio Savelli; Lima, Marcus Vinícius Gonçalves; Santi, Adalberto; Vendruscolo, Marice Cristine; Magalhães, Marcio Osvaldo Lima (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
Many consumers have been looking for increasingly safe foods, without agrochemicals, as those produced in organic systems. An alternative to this is the use of techniques that minimize the use of agrochemical inputs. Thus, this study aimed to evaluate the effect of cow urine application on the performance of radish crops. The experiment was carried out in Tangará da Serra, Mato Grosso, Brazil. The experimental design was a randomized block with five treatments and four replications. The treatments employed were: Organomineral leaf fertilizer (Platon-25®) and four doses of cow urine (0 mL; 35 mL; 70 mL and 105 mL). The variables evaluated were: tuberous root diameter, tuberous root length, shoot fresh mass, root fresh mass, tuberous root weight, root length. Application of cow urine, regardless of dose, influenced significantly radish development. At the 70 mL dose of cow urine, the plants showed the same development as those that received the application of organomineral fertilizer. Cow urine provided better radish performance when compared to organomineral fertilizer for most of the variables analyzed, showing that for the conditions of the study, the 105 mL dose of cow urine can be used as a foliar biofertilizer in the radish crop.